Analisis Ketahanan Hidup Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis di Rumah Sakit Kota Makassar - Iva Hardi Yanti; Ida Leida Maria; Nurhaedar Jafar (Jurnal Forum Kesehatan, 2018)
Chronic renal failure incidence has increased every year, Indonesian renal registry through 2012 on kidney patients Chronicle up to 100,000 thousand patients and predicted continued to experience increased. Research purposes, to know the proportions and the most influence on prognosis of survival of patients who undergo hemodialysis chronic renal in Makassar city hospital by 2012-2015. This type of research, analytic observational cohort retrospective design, the collection of data with a data search medical record, analyzed by kaplan meier and cox regression. The results showed the proportion of patients ' survival year 1, 2, and 3 respectively around 28%,15%, and 13%. The prognosis of the most influential i.e. age and albumin. The proportion of survival of patients aged >55 years amounted to 0.04 (4%) at the end of the 24th month of observation than the age of 55 years < 0.000 (0%) in the month to-38. The group aged >55 years 1,438 times likely experienced the event than age ≤55 years. The proportion of patient survival by albumin <3.5 grams/dl amounted to 0.08 (8%) end of the 24th month of observation than patients with albumin ≥ 3.5 g/dl of 0.000 (0%) the risk of 38 patients with albumin 3.5 grams/dl < 1,297 times likely experienced the event than patients with albumin ≥ 3.5 g/dl. Kesimpulanya Health Services Center, is expected to detect early kidney Chronicles events in the age related and made examination of albumin as one checks the patient's diagnosis.